Levels of bacterial and chemical pollutants in Euphrates River in Samawah, Iraq - Hayder H. Abed; Zainab Y. Kadhim; Saif M. Abed; Zahra S. Mahdi (World Journal of Experimental Biosciences, 2016)
In present study biological and chemical pollution of Euphrates River in Samawah city in Iraq were studies. Samples were collecting from three places; al-Majed area, Samawah city and al-Khader city. This study included analysis of five heavy metals in the river (Pb, Fe, Cu, Cd and Zn); the study also included some bacterial pollution in the river in the three places. The study involving total Plate Count of the aerobic microbes in addition to isolation and identification of some bacterial isolates that present in the stream of river in the studied places. The results showed differences in concentration of metals in the river and increase in the concentrations, especially in al-Khader city due to pollution in Samawah city also the bacteriological study showed presence of different bacterial species; Escherichia coli (24.5%), Enterobacter aerogenes (10.11%), Salmonella spp (4.79%), Klebsiella pneumonia (20.3%), Proteus mirabilis (11.45 %), Proteus vulgaris (7.55%), Pseudomonas aeruginosa (7.21), Staphylococcus aureus (8.91%), Staphylococcus epidermids (5.18 %), E. coli represented the main bacteria as compared with others bacteria. The study showed increase in the five studies heavy metals concentrations in AL-Khader city specifically in case of copper and lead.
Keywords: Al-Khader, Al-Majed, Euphrates, Heavy metals, Samawah.